Lizards - Marsh, Laura (Washington, D.C. : National Geographic, 2012)
Photographs and text introduce young readers to different kinds of lizards, covering geckos, iguanas, komodo dragons, chameleons, and other types, and including instructions for a related activity.
2.3
K-3
460L
M
Keywords: Lizards -- Juvenile literature; Lizards